Thermal Drone Technology Used to Capture Thermoregulation in Wild Sumatran Elephants - Raden Danang Wijayanto; Aryo Adhi Condro; Dede Aulia Rahman (Bogor Agricultural University, Indonesia, 2023)
Drone technology plays a critical role in supporting conservation efforts for endangered species, not only in terms of species monitoring within various landscapes, but also potentially when applied to behavioral studies to investigate interaction patterns and response to environmental change. We tested a thermal drone to investigate thermoregulation and surface temperature of wild Sumatran elephants in the lowland tropical forest of Jambi, Indonesia. Thermoregulation data was obtained using RGB images and videos, while temperature values were measured from thermal images (R-JPEG) extracted into TIFF equipped with pixel temperature. We detected a visual thermoregulation mechanism known as mud bathing. Our study demonstrated that the trunk functions to draw mud and throw it onto the head, back, and stomach, the tail functions to distribute the mud to all parts of the back of the body, while the ears flapped to keep head temperature cool. Our measurements showed that the surface temperature of Sumatran elephants is between 28.9-30.3Â°C. The head had a relatively lower temperature than other body parts. This study also revealed that the environmental humidity variable significantly affects the elephant's temperature rise. The use of drone technology for future behavioral studies is recommended as it accurately provides high quality data and can be widely used in any type of terrain.